Internet of Things (IoT) and Water Crisis - Kadar H.H.; Rafee P.A.A.; Sameon S.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Communication; Water; Water management; Arduino; Information and Communication Technologies; Internet of Things (IOT); IT impact; ITS Services; resources; SMART2L; Water crisis; Internet of things